2021
DOI: 10.4269/ajtmh.20-1398
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Evaluation of Immunoglobulin G Response after Chikungunya Virus Infection

Abstract: Current chikungunya antibody prevalence and titers are likely to differ based on exposure rates before the 2006 reemergence. For vaccine usage, such data are of immense importance. This study addresses age-stratified IgG titers and its subtypes in Pune, India, endemic for the disease. One hundred seventy serum pools (791 individuals with prior chikungunya exposure, age stratified) from exposed and 15 samples from acute disease phase were screened. Inactivated chikungunya virus (CHIKV)–based indirect ELISA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…A similar trend was observed among age groups in studies conducted in India, Singapore, and Nigeria [ 52 , 56 , 58 ]. The relationship between increasing age and CHIKV susceptibility has been attributed to the increased degree of exposure and impaired immune function in the elderly population [ 58 , 59 ]. However, the seroprevalence of anti-CHIKV IgM antibodies was highest among children ≤ 5 years old and adults ≥ 46 years old, which is indicative of acute infection in the population.…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was observed among age groups in studies conducted in India, Singapore, and Nigeria [ 52 , 56 , 58 ]. The relationship between increasing age and CHIKV susceptibility has been attributed to the increased degree of exposure and impaired immune function in the elderly population [ 58 , 59 ]. However, the seroprevalence of anti-CHIKV IgM antibodies was highest among children ≤ 5 years old and adults ≥ 46 years old, which is indicative of acute infection in the population.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of antibodies that serve as a critical barrier against viral infection was also demonstrated for CHIKV (19).…”
Section: Discussionmentioning
confidence: 97%
“…Arankalle’s group aimed to evaluate envelope-specific immune responses in individuals with CHIKV infection in 2006. The findings demonstrated that lower levels of IFN-γ may be associated with the severity of the disease in these individuals, and T cell epitopes recognized on the envelope region of CHIKV by all patients [ 208 , 209 ]. This team intended to create potential vaccines using either recombinant CHIKV-E2 protein or chemically inactivated whole CHIKV.…”
Section: Chikv Research: Indian Scenariomentioning
confidence: 99%